The displacement study of 99mTc‐DTPA—Human serum albumin binding in presence of furosemide and metformin by using equilibrium dialysis and molecular docking. Issue 12 (21st October 2019) - Chemlal, Laila; Akachar, Jihane; Makram, Sanaa; Zoubir, Brahim; Cherrah, Yahia; Eljaoudi, Rachid; Ibrahimi, Azeddine; Faouzi, Mly A.
Abstract: The 99m Tc‐DTPA (Technetium 99m diethylenetriaminepentaacetic acid), is a radiopharmaceutical used in renal scintigraphy. The human serum albumin (HSA) binding site(s) for the 99m Tc‐DTPA have never been characterized. This study will cover in vitro the binding rates of 99m Tc‐DTPA on HSA and the 99m Tc‐DTPA competition interactions with two drugs having known human serum albumin binding sites. Furosemide (FUR) and metformin (MET) were added to 99m Tc‐DTPA solution (weight ratios 1/1 vol:vol) followed by the quantification of 99m Tc‐DTPA binding rates to HSA (40 g/L) using equilibrium dialysis and the qualification of this binding using Molecular Modeling methods. The 99m Tc‐DTPA binding rates to human serum albumin increased with the highest concentration. Both drugs FUR and MET displaced 99m Tc‐DTPA binding. 99m Tc‐DTPA could bind to human serum albumin in many locations in site I and I‐II, but strongly bound to site I through hydrogen bonds.